Characterization and Utilization of Woka (Saribus rotundifolius (Lam.) Blume.) Based on Local Wisdom of the People of Bolaang Mongondow Regency - Wawan Nurmawan; Hengki D. Walangitan; Maria Y. M. A. Sumakud; Euis F. S. Pangemanan (Postgraduate, University of Mataram, 2025)
Woka (Saribus rotundifolius (Lam.) Blume.) is a palm tree that has significant ecological and socio-cultural value for the community of Bolaang Mongondow. However, local knowledge about its use and characteristics is threatened by extinction due to modernization. This study aims to: (1) identify the morphological characteristics of the woka plant, and (2) document the forms of utilization based on the local wisdom of the community of Bolaang Mongondow in managing woka. This study used qualitative methods with an ethnobotanical approach. Data were collected through field observations, in-depth interviews with key informants (traditional leaders and craftsmen), and documentation studies. The results show that woka has distinctive morphological characteristics, such as round fan-shaped leaves (rotundifolius) and strong stems. Woka has a wide range of uses, especially its leaves, which are used as roofing material for traditional houses (baloi), woven crafts for traditional ceremonies, and as food wrappers. Local wisdom is reflected in the knowledge system of sustainable harvesting techniques, traditional rules of harvesting, and beliefs that support the preservation of woka. It is concluded that woka is not just a plant but an integral part of the local cultural identity and ecosystem. This documentation is expected to serve as a database for the conservation and sustainable development of the economic value of woka.